Improving clinical paediatric research and learning from COVID-19: recommendations by the Conect4Children expert advice group - KARADAĞ, BÜLENT TANER (My University, 2022)
© 2021, The Author(s).Background: The COVID-19 pandemic has had a devastating impact on multiple aspects of healthcare, but has also triggered new ways of working, stimulated novel approaches in clinical research and reinforced the value of previous innovations. Conect4children (c4c, www.conect4children.org) is a large collaborative European network to facilitate the development of new medicines for paediatric populations, and is made up of 35 academic and 10 industry partners from 20 European countries, more than 50 third parties, and around 500 affiliated partners. Methods: We summarise aspects of clinical research in paediatrics stimulated and reinforced by COVID-19 that the Conect4children group recommends regulators, sponsors, and investigators retain for the future, to enhance the efficiency, reduce the cost and burden of medicines and non-interventional studies, and deliver research-equity. Findings: We summarise aspects of clinical research in paediatrics stimulated and reinforced by COVID-19 that the Conect4children group recommends regulators, sponsors, and investigators retain for the future, to enhance the efficiency, reduce the cost and burden of medicines and non-interventional studies, and deliver research-equityWe provide examples of research innovation, and follow this with recommendations to improve the efficiency of future trials, drawing on industry perspectives, regulatory considerations, infrastructure requirements and parent–patient–public involvement. We end with a comment on progress made towards greater international harmonisation of paediatric research and how lessons learned from COVID-19 studies might assist in further improvements in this important area.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Health Sciences; Klinik Tıp (MED); Klinik Tıp; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics, Perinatology and Child Health